From Health Geography to botanical identification: um itinerário biogeográfico para promover a saúde - Pereira, Martha Priscila Bezerra (Technical and Scientific Journal Green Cities, 2025)
The action of explicitly uniting knowledge from two or more áreas emerged in the 1960s with the aim of resolving a certain situation, initially called interdisciplinarity, but seeking transdisciplinarity. Uniting Geography, Biology and the field of Health in order to promote health would be na attempt to carry out this transdisciplinarity in a little used way. The objective of this work was to show the importance of botanical identification for health promotion and its contribution to Health Geography. It was based on the Systemic Scientific Method. The design used was: a) undestanding of the biome in which the study área is located; b) Identification of the physiognomic-ecological system and land use; c) detailing the types of vegetation by municipality visited; d) Search for websites and applications about medicinal plants studied in the municipalities Where the field will be carried out; e) Search for more abundant families in each municipality studied; f) identification of fotos of plants or Other living beings in each location under study; g) field work and; h) organization of information. As main results, it was observed that botanical identification helps in the confidence in the use of a certain medicinal plant and in contact with nture in a more conscius way, and even generating income in a sustainable way, facilitating the processo f promoting health. Finally, research involving botanical identification for medicinal use can promote health in several aspects, including local and regional development.